2011
DOI: 10.1021/ie201189z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nano Calcium Oxide from a Gastropod Shell and the Performance Evaluation for Cr (VI) Removal from Aqua System

Abstract: A spongy, porous nano calcium oxide (NC) with point zero charge of 11.80 was synthesized using the shell of a Gastropod (Achatina achatina) via the sol–gel technique. The ability of the NC to adsorb Cr (VI) from aqueous solution was assessed systematically in a batch process via isothermal, kinetic, and variable process optimization procedure. The sorption data had the best fitting for the Langmuir isotherm model and the monolayer sorption capacity (q m, mg/g) value of 125 mg/g was obtained. The initial soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Some researchers showed that CaO catalyst in nano-dimension will render amazing level of performance in terms of product selectivity and catalytic reactivity. This includes the transesterification reaction of triglyceride with methanol [13,14], and reacted as chemisorbents for toxic gases, chlorinated or phosphorus-containing compounds and pollutant in water [15,16]. CaO is capable of providing high surface area-to volume ratio in nano-crystalline structure, which is five times more in the number of active sites per unit area [17], thus offering higher basicity of catalyst which shall have positive effects on various reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers showed that CaO catalyst in nano-dimension will render amazing level of performance in terms of product selectivity and catalytic reactivity. This includes the transesterification reaction of triglyceride with methanol [13,14], and reacted as chemisorbents for toxic gases, chlorinated or phosphorus-containing compounds and pollutant in water [15,16]. CaO is capable of providing high surface area-to volume ratio in nano-crystalline structure, which is five times more in the number of active sites per unit area [17], thus offering higher basicity of catalyst which shall have positive effects on various reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies were discussed on the preparation methods for Ca(OH) 2 nanoparticles including sonochemical technique [4,21], hydrogen plasma-metal reaction [5], sol-gel method [22][23][24], hydrothermal method [25], homogeneous and heterogeneous phase syntheses [26][27][28][29] and precipitation method [30,31]. However, these techniques come with its own limitations which are high cost of organic solvents and chemical reagents that required as CaO starting precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these, adsorption has been proven to be one of the best alternative techniques due to its simplicity, low cost and robustness (Atia, 2008;Sarkar et al, 2010). Numerous adsorbents like metal oxide, chitosan, industrial waste material, biomaterials, activated carbon and clays have been assessed for the removal of Cr(VI) from water and wastewater by different researchers (Hu et al, 2003;Lee et al, 2005;Bhattacharyya and Sen Gupta, 2006;Liu et al, 2006;Oladoja et al, 2012;Shroff and Vaidya, 2012). In most of the studies, these materials were found to have low adsorption capacity and slow kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related to calcium sources [2][3][4] used raw material mussel shells, fish scales, and gastropod shells respectively. Sol-gel method using HCl and NaOH produced calcium from catfish bone by 19.87% [5].…”
Section: Introductionmentioning
confidence: 99%